Enhanced fuzzy tungsten growth in the presence of tungsten deposition. (8th January 2020) - McCarthy, Patrick; Hwangbo, Dogyun; Bilton, Matthew; Kajita, Shin; Bradley, James W.
Abstract: Using a magnetron sputtering device operating in helium, fibre-form 'fuzz' has been grown on tungsten samples in the presence of a significant auxiliary source of depositing tungsten. In this system, fuzzy tungsten was grown over a range of helium ion fluences, , sample temperatures and helium ion energies, but with operator control over the tungsten atom-to-helium ion arrival rate ratio at the sample (from 0.003 to 0.009). In the presence of tungsten deposition, it appears that the fuzz growth has two distinct stages: at low to intermediate helium ion fluence the fuzzy layer thickness follows the expected diffusive law augmented by approximately the 'effective' thin film thickness of deposited tungsten; at high fluences the fuzz thickness increases very steeply with . These observations are explained through the increase in the porosity of the fuzzy layer as it reaches thicknesses larger than ̃1 m. It was observed that during the second phase of fuzz growth the thickness was highly dependent on both the sample temperature and the tungsten atom-to-helium ion arrival rate ratio. For the same helium ion exposure, an increase in the sample temperature from 1050 to 1150 K lead to a six-fold increase in the fuzzy layer thickness, whilst increasing the tungsten atom-to-helium ion arrival rate ratio over the full range produced a two-fold increase in the thickness. Microscopy and electron diffraction studies of the grown structures show clearly helium bubbles within polycrystalline tendrils.